Degeneration grade of a femoropatellar joint and functional status of a knee joint - Olesiak, Beata; Przedborska, Agnieszka; Raczkowski, Jan Wojciech (Journal of Education, Health and Sport, 2019)
Aim of the paper: The aim of the study was to assess the impact of degeneration of femoropatellar joint cartilage on selected variables related with a knee joint functionMaterial and methods: The studied group consisted of 50 patients that were diagnosed, through ultrasonography, changes in femoropatellar joint cartilage according to the Outerbridge classification. The data was collected with usage of a self-designed questionnaire. The study included pain assessment according to the VAS scale, Zohlen’s test, rectus femoris muscle test. Results: There is statistically significant correlation between the grade of degenerative changes and age (p<0.0001), and the size of the body mass index (p=0.0098). With the increase of the degenerative changes grade, the percentage of patients with the positive result of Zohlen’s test, and with the positive result of the quadriceps muscle test increases significantly (p=0.0001). Also, it is observed more frequent (p<0.0001) presence of the fluid in case of the III and IV grades of degeneration. With the increase of degeneration grade of cartilage, intensification of pain symptoms, measured in the VAS scale, significantly (p=0.0083) increases. Statistically significant (p=0.0001) relationship was also observed between the presence of fluid in the joint and the result of the quadriceps muscle function test (with the presence of the fluid, the percentage of patients with the positive test result increases).Conclusions: 1. Degenerative changes of femoropatellar joint cartilage affect quadriceps muscle dysfunction. 2. Pain symptoms of femoropatellar joint cause motion deformity of the knee joint. 3. Increased amount of the joint fluid is related with a higher grade of the joint degeneration.